Os alunos com necessidades educacionais especiais nos diferentes espaços-tempos da escola : aspectos cotidianos e não cotidianos - Mendes, Katiuscia Aparecida Moreira de Oliveira (2010)
Taking into consideration the lack of specific studies in the area of scholastic Physical Education and the inclusion of students with special educational needs at regular schools, the research aims at analyzing the process of inclusion of students with special educational needs in different space-time of the school, emphasizing Physical Education. It was chosen a research in the historical-cultural perspective, with a qualitative approach, characterized with a study case with ethnographical inspiration. There were observations, totalizing 112 hours, in a sixth grade group of a municipal elementary school in the district of Vitória, state of Espírito Santo. The empirical data permitted to analyze two distinct cases: a) a boy with low sight who had some access to knowledge (scientific, art, among others) through school and the school experience enabled him to pass through barriers; b) a boy with Down syndrome who occupied his time with school activities only, and his academic success was endangered by the lack of pedagogical proposals